Upaya Peningkatan Kunjungan Posyandu Balita di Praktek Mandiri Bidan Sary Rahayu, S. ST - Khairulisni Saniati; Asri Fitri Yati; Miftah Chairunnisa; Silvia Finida Hannisa; Ummy Khairussyifa (Universitas Maritim AMNI Semarang, 2024)
Monitoring of the growth and development (fall) of toddlers is carried out routinely by health workers to find out the condition of toddlers, whether there are irregularities in the fall of toddlers so that they can be handled immediately, therefore this monitoring is very important. Growth monitoring is carried out by weighing body weight and measuring limbs, as well as measuring head circumference according to the schedule. Monitoring of development was carried out by giving KPSP (Developmental Pre-Screening Questionnaire), TDD (Hearing Test), TDL (Visual Ability Test), KMME (Questionnaire for Mental and Emotional Problems), CHAT (Checklist for Autism in Toodlers), and GPPH (Attention Deficit and Hyperactivity Disorder) (Ministry of Health of the Republic of Indonesia, 2014).